2020
DOI: 10.1109/jlt.2020.2972367
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Demonstration of Spatial Channel Networking Using SDM/WDM Hierarchical Approach for Peta-b/s Optical Transport

Abstract: This article reports on a proof of concept demonstration of a recently proposed spatial channel network (SCN) that was conducted over an SCN testbed that comprises low-loss hierarchical optical cross-connect (HOXC) prototypes and four-core multicore fiber links. The HOXC prototypes used in the testbed are based on sub-matrix-switches and core selective switches both implemented with commercially available discrete optical switches. Using these two types of HOXC prototypes, the spatial channel networking includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…As described in Section 1, refs. [6][7][8][9][10][11][12][13][14][15][16] have conducted a series of studies on SCNs and demonstrated the practicability, scalability, reliability, and economical efficiency of SCNs. In Figure 1, the optical layer can be divided into an SDM layer and a WDM layer, and the optical nodes are considered as HOXCs, consisting of WXCs and SXCs in SCNs.…”
Section: Spatial Channel Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…As described in Section 1, refs. [6][7][8][9][10][11][12][13][14][15][16] have conducted a series of studies on SCNs and demonstrated the practicability, scalability, reliability, and economical efficiency of SCNs. In Figure 1, the optical layer can be divided into an SDM layer and a WDM layer, and the optical nodes are considered as HOXCs, consisting of WXCs and SXCs in SCNs.…”
Section: Spatial Channel Networkmentioning
confidence: 99%
“…As described in Section 1, refs. [6][7][8][9][10][11][12][13][14][15][16] have conducted a series of studies on SCNs and demonstrated the practicability, scalability, reliability, and economical efficiency of SCNs.…”
Section: Spatial Channel Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…As SDM technology began to gather much attention, some experimental demonstrations on multigranular (time, wavelength, and space) optical networks based on a multi-core fiber (MCF) link and a high port count SMF switch were reported [14][15][16]. The spatial channel network (SCN) architecture [17][18][19][20] was recently proposed as another approach to take full advantage of the spatial dimension. In an SCN, the current optical layer evolves into hierarchical wavelength division multiplexing (WDM) and SDM layers, and an optical node is decoupled into a spatial cross-connect (SXC) and a conventional WXC to form a hierarchical optical cross-connect [18].…”
Section: Introductionmentioning
confidence: 99%
“…As SXC architectures with growability and reliability, our research group recently proposed novel SXC architectures [14], [16] based on a sub-matrix switch and a new type of optical spatial switch, which is referred to as a 1 × k core selective switch (CSS). Recently, we demonstrated the feasibility of spatial channel networking including spatial bypassing, spectral grooming, spatial-lane change, and spatial-channel protection over a spatial channel network testbed that comprised two types of low-loss SXC prototypes connected with four-core fibers [18], [19]. Fig.…”
Section: Introductionmentioning
confidence: 99%